Improving Employee Performance Through Organizational Commitment With Job Satisfaction As a Mediating Variable - Purnomo Agus Nugroho; Sutianingsih Sutianingsih (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to understand how job satisfaction can mediate organizational commitment and employee performance. In this study, quantitative research methods were used. Data were collected with the help of questionnaires and a sample of 115 workers. Path analysis and descriptive analysis are the data analysis methods used. Research findings show that all variables have a positive effect from 1) organizational commitment impacts employee performance variables. 2) Organizational commitment has an impact on job satisfaction. 3) Job satisfaction has an impact on employee performance. 4) The results of this study state that indirect influence is more substantial than direct influence, then organizational commitment is used as an intermediary variable between job placement variables and employee performance. Keywords: organizational commitment, job satisfaction, employee performance